(untitled) (Journal of Academic Research, 2024)
The research aims to know the quality of university education for people with special needs in the Collegeof Arts University of Benghazi from the viewpoint of faculty members. The researcher used the descriptive method because it suits the nature and objectives of the research. The research community consisted of faculty members at the Faculty of Arts, University of Benghazi. The research sample was chosen intentionally from the departments of the Faculty of Arts, University of Benghazi, and it is: .(Islamic studies, Arabic language, psychology, sociology) The sample number was (20) faculty members. After reviewing scientific references and previous studies, the researcher designed a questionnaire consisting of: It consists of (30) questions, and consists of three scales (high, medium, low.) After the researcher distributed the questionnaire to the members of the research sample and collected it, they unpacked The data were analyzed statistically and they reached the following conclusion: The low level of quality of university education for people with special needs at the Faculty of Arts, University of Benghazi.